Characteristics and Outcomes in Head and Neck Sarcomatoid Squamous Cell Carcinoma: The Cleveland Clinic Experience. (July 2021) - Mingo, Katie M.; Derakhshan, Adeeb; Abdullah, Neelab; Chute, Deborah J.; Koyfman, Shlomo A.; Lamarre, Eric D.; Burkey, Brian B.
Objectives: To analyze characteristics, treatment outcomes, and prognostic factors of sarcomatoid squamous cell carcinoma of the head and neck. Study Design: Retrospective chart review. Setting: Tertiary care center. Subjects and Methods: Fifty-five patients were treated for sarcomatoid squamous cell carcinoma of the head and neck between 1996 and 2018. Data collection included clinical history, tumor characteristics, pathology, treatment modality, and outcomes. Mean follow up was 17.1 months. Cox univariate analysis was used to evaluate for associations with locoregional recurrence, distant metastasis, and overall survival. Results: Most patients were white males with a smoking history and median age 66 years (range 41-92) at diagnosis. Twenty-two percent had prior head and neck radiation. Tumor site was most frequently oral cavity (41.8%), followed by larynx (29.1%), and oropharynx (16.4%). Half presented with early T stage disease (15.5% T0, 12.7% T1, 30.9% T2) and the remainder with late stage disease (16.4% T3, 34.5% T4). Locoregional recurrence rate was 60.0%, metastatic recurrence was rate 21.8%, with median time to recurrence of 4 months and mean overall survival of 20 months. Presence of lymphovascular space invasion was statistically associated with locoregional recurrence ( P  = .018, HR 3.55 [95% CI 1.24, 10.14]) and poorer overall survival ( P  = .015, HR 2.92 [95% CI 1.23, 4.80]). Treatment with multimodality therapy was associated with decreased locoregional recurrence ( P  = .039, HR 0.39 [95% CI 0.16, 0.95]) but did not impact overall survival. Conclusion: Sarcomatoid squamous cell carcinoma remains a rare and aggressive disease variant with high recurrence rates and high mortality. High risk features such as lymphovascular space may indicate the need for more aggressive therapy.